The Effectiveness of Choosing Language Diction by the Principal in Managing Islamic Education Institutions (Jacques Derrida's perspective) - Rateh Ninik Pramitasary; Isa Anshori; Budi Haryanto (Proceedings of The ICECRS, 2020)
This paper discusses the effectiveness of English Diction election by Headmaster in Managing Institutions of Islam. Language consists of several ranks grammatical include words, phrases, clauses, and sentences. The word is the lowest level and the sentence is the highest level. When you write, the word is a key element in the effort to write. Therefore, a number of words in Indonesian should be well understood, so that one's ideas and messages can be easily understood. Thus, the words used to communicate to be understood in the context of the paragraph and discourse. The word as an element of the language, can not be used arbitrarily. However, these words should be used by following the correct rules. This Pnelitian use This research is qualitative descriptive study which is expected to reveal a variety of information-description rigorous analysis and meaningful. Sources of data in this research include the principals of this research study ju analysis pusataka research is to investigate the theory of structuralism and Derrida Jacquest dekonstruktifisme. Data was collected by interview, observation, and documentation and study the literature. Adapaun data analysis techniques through the stages of data reduction, data presentation and analysis of data. The results of such research are (a) the selection of appropriate language diction will lead to a successful school leadership to manage and develop the advanced study lead.